DNA Test of paternity in Islamic Law: Implications for children born less than minimum gestation period in Malaysia - Haneef, Sayed Sikandar Shah (Hamdard Foundation, 2016)
The Problem of children born within the marriage but less than six months is a disputed issue in Islamic law. Some accept then as legitimate based on istihaq and others do not. This paper argues for bringing the DNA discussion as another mechanism.